ANALISIS YURIDIS TERHADAP PENERBITAN AKTA JUAL BELI TANAH DI KABUPATEN JEMBRANA PADA KANTOR NOTARIS/PPAT I KOMANG DIVO MAHAYAKTI HERIADI,S.H.,M.KN - I Komang Luki Nanda; Anak Agung Putra Arjawa; I Wayan Bandem (Yayasan Nusantara Hasana Berdikari, 2023)
Preparatory Stages for Making a Deed: Transfer of land rights as specified in article 1320 of the Civil Code. Preparation and Signing of the Deed by presenting the parties, two or more witnesses, the Approval Witness, and the PPAT reading the Sale and Purchase Deed in front of the parties. Registration of Transfer of Rights is regulated in Article 98 PMNA/Head of BPN No. 3 of 1997 concerning implementing provisions of Government Regulation Number 24 of 1997 concerning Land Registration. Apart from the provisions of Article 98 PMNA/Head of BPN No. 3 of 1997, buying and selling regarding use rights must also follow the provisions of Article 43 of the Basic Agrarian Law (UUPA). Issuance of Land Sale and Purchase Deed: has a legal basis in Article 5 UUPA which states that the applicable agrarian law is customary law. Government Regulation no. 24 of 1997 that the Deed of Sale and Purchase is an important document, Government Regulation Article 37 paragraph (1) states that land ownership will only be recognized by the state if a Deed of Sale and Purchase is issued by PPAT. PPAT fees in Article 32 paragraph (1) PP 24/2016, do not require either party to pay, everything is according to the agreement of both parties. Issuance of a Deed of Sale and Purchase, 2 original copies must be made, one kept by the PPAT and the other at the Land Office for registration of transfer of name. The seller and buyer receive a copy of the deed from PPAT. Obstacles faced by PPAT in issuing the Deed of Sale and Purchase: Internal factors, namely the technical aspect (implementation) and the bookkeeping aspect. External factors, namely many transfers of land rights are carried out privately, the public lacks knowledge about the importance of registering transfers of land rights, and the process costs up to the end are relatively expensive. The obstacle is that many people in rural areas register the transfer of their land rights through the Village Head.